Delay analysis of converged optical‐wireless networks with quality of service support. Issue 5 (1st September 2014) - Vardakas, John S.; Moscholios, Ioannis D.; Zorba, Nizar; Logothetis, Michael D.; Verikoukis, Christos V.
Abstract : The convergence of two popular access technologies, namely Worldwide interoperability for Microwave Access (WiMAX) and passive optical network (PON) is a promising access solution that combines the mobility feature of WiMAX and the ample bandwidth of PONs. In such a converged optical‐wireless access network, the provision of quality of service (QoS) support is a challenging issue, mainly because of the different bandwidth allocation mechanisms of the two access technologies. Since the considered convergence seems to be dominant, it deserves assiduous analysis and evaluation. In this study, the authors investigate the delay performance of a converged optical‐wireless network that provides QoS support by considering multiple service‐classes with different priorities. In the wireless domain, the IEEE 802.16 standard is applied, whereas in the optical domain a wavelength division multiplexing ethernet PON provides connectivity to both wired and wireless users. The authors present an analytical framework for the calculation of the average end‐to‐end packet delay of each service‐class, by developing two queuing models for each domain of the converged network. The end‐to‐end delay is calculated as the sum of the queuing delay in both domains, and the transmission and propagation delay in the optical domain. The accuracy of the proposed analysis has been verified by simulation and found to be quite satisfactory.